Peningkatkan Pembelajaran Saintifik Di TK Pelita Pertiwi Kajar Trangkil Pati - Khosyi'in, Nur (Kifah: Jurnal Pengabdian Masyarakat, 2023)
The aim of teaching and learning assistance is to improve the quality of learning at Pelita Pertiwi in Kajar kindergarten as our main goal in assisting the learning process with the method of applying a scientific approach, designed in such a way that students actively construct learning concepts according to what they need, by carrying out teaching and learning activities. Using this method of applying a scientific approach can improve the quality of children's learning, from this learning children can carry out activities of observing, asking questions, gathering information, associating and communicating, this method can stimulate children to be more active and as a way of teaching children to be able to solve problems or problem solving. In implementing this scientific learning model, children are the center of learning (student centered approach), this means that students must be able to organize themselves and be able to participate in activities well through the media and learning resources provided, while the teacher is only a facilitator. Because the core objective of scientific learning is designed to activate the role of students from being accredited to accepting to becoming discoverers and communicating science based on the observations they produce. Keywords: mentoring, learning, scientific methods.